(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Allergic conditions strides by food sensitization and has lousy impact on the immune system of individuals and has also provokes IgE antibody that spearhead the activation of inflammatory mechanism. The aim of this current research is to evaluate the effect and the preponderance rate of symptoms appearance in garlic and onion allergies. Methodology: The cross sectional study was conducted among general population (N=200) of Karachi from January 2017 to October 2017. Result: Through current study it is revealed that only 50 out of 200 personals showed significant results. Diverse type of symptoms used to appearance in individuals suffering with onion and garlic allergies and it is importantly notifying that some genetic correlation is supposed to exists in these individuals for transmit of these allergies. Conclusion: Onion and garlic both are esoteric allergies, these allergies rate are increasing in our population and patients suffered from very annoying symptoms including some fatal conditions also. Genetic relation is another link of developing these allergies. Limited data has been reported yet but it should be further investigated to evaluate multiple other factors contributing to these allergies. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.871-877